Resource Constraints and the Role of Executive Disposition Strategies in Women's Empowerment Policies in Ternate City - Musdalifah Musdalifah (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The women’s empowerment program through home-based industries in Ternate City is a strategic initiative by the local government to promote economic independence and gender equality. However, its implementation faces various challenges, especially the limited availability of resources such as budget, personnel, and supporting facilities. This study aims to analyze the role of implementers’ disposition, namely attitudes, commitment, and coordination capacity in ensuring the effectiveness of policy implementation under such constraints. Using a descriptive qualitative approach, data were collected through interviews and documentation, and analyzed thematically. The findings show that implementers’ disposition is a critical factor in policy success. Strong commitment and cross-sector coordination have enabled the program to continue operating adaptively and responsively, despite structural limitations. This study emphasizes that human factors particularly the disposition of implementers play a strategic role in bridging formal policy with field realities.